From models to pathogens: how much have we learned about Streptococcus pneumoniae cell division?. (15th July 2013) - Massidda, Orietta; Nováková, Linda; Vollmer, Waldemar; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary Streptococcus pneumoniae is an oval‐shaped Gram‐positive coccus that lives in intimate association with its human host, both as a commensal and pathogen. The seriousness of pneumococcal infections and the spread of multi‐drug resistant strains call for new lines of intervention. Bacterial cell division is an attractive target to develop antimicrobial drugs. This review discusses the recent advances in understanding S. pneumoniae growth and division, in comparison with the best studied rod‐shaped models, Escherichia coli and Bacillus subtilis. To maintain their shape, these bacteria propagate by peripheral and septal peptidoglycan synthesis, involving proteins that assemble into distinct complexes called the elongasome and the divisome, respectively. Many of these proteins are conserved in S. pneumoniae, supporting the notion that the ovococcal shape is also achieved by rounds of elongation and division. Importantly, S. pneumoniae and close relatives with similar morphology differ in several aspects from the model rods. Overall, the data support a model in which a single large machinery, containing both the peripheral and septal peptidoglycan synthesis complexes, assembles at midcell and governs growth and division. The mechanisms generating the ovococcal or coccal shape in lactic‐acid bacteria have likely evolved by gene reduction from a rod‐shaped ancestor of the same group.